Exploring the Research Trends of Media Training Kit in Vocational Education through Bibliometric Analysis - Vivi Oktavia; Dedy Irfan (Postgraduate, University of Mataram, 2024)
This study aims to explore research trends on media training kits in vocational education, which have become crucial in preparing skilled workers to meet modern industry demands. Media training kits are essential tools that bridge the gap between theoretical knowledge and practical application, simulating real working conditions to enhance students' skills. Despite their growing use, research on their effectiveness, design, and innovation remains fragmented and poorly structured. A bibliometric analysis was conducted using the Scopus database to systematically map the landscape of media training kit research, identifying key publications, influential authors, major journals, and prevalent research topics. The analysis revealed significant gaps in the literature, underlining the need for continuous research to evaluate technological advancements, such as virtual simulations and augmented reality, in training kits. Results highlight the importance of integrating interactive and adaptive training kits to support evolving pedagogical and technological approaches in vocational education. This study provides valuable insights for researchers, educators, and policymakers, helping them make informed decisions to enhance the development and application of media training kits, ultimately improving the quality and relevance of vocational education in response to industry needs.